2019
DOI: 10.18388/abp.2018_2646
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil does not affect the proliferation of human lymphocytes in the in vitro transplant model

Abstract: Sildenafil is used in the treatment of erectile dysfunction and pulmonary arterial hypertension. Numerous studies revealed beneficial effects of its use in renal, liver, heart and bone marrow transplant recipients. Some reports suggested that the drug modulates the function of the immune system, however, its influence on antigen-induced proliferation of lymphocytes remains unknown. Thus, the aim of the study was to investigate the effects of sildenafil on human peripheral blood mononuclear cells (PBMCs) prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
2
0
0
Order By: Relevance
“…Result of current experiment corresponds to our previous findings of downregulating NK cells activity by SC [8]. Kaleta and Boguska reported that SC did not influence T cell 3 Journal of Immunology Research proliferation and had no cytotoxic effect on T cells which is in line with our observations [21]. Researchers in opposite to our findings show that cultures of lymphocytes of healthy men treated with sildenafil citrate have an increased level of TNF-α in supernatants collected from PBMC culture [22].…”
Section: Discussionsupporting
confidence: 92%
“…Result of current experiment corresponds to our previous findings of downregulating NK cells activity by SC [8]. Kaleta and Boguska reported that SC did not influence T cell 3 Journal of Immunology Research proliferation and had no cytotoxic effect on T cells which is in line with our observations [21]. Researchers in opposite to our findings show that cultures of lymphocytes of healthy men treated with sildenafil citrate have an increased level of TNF-α in supernatants collected from PBMC culture [22].…”
Section: Discussionsupporting
confidence: 92%
“…Zhu et al reported that PDE5 played a dominant role in regulating cGMP transitions that inhibited cell growth and controlled the susceptibility to apoptosis in the pulmonary endothelium [ 56 ]. Nevertheless, our specific flow cytometry analysis revealed that the drug did not affect idNK cell apoptosis, at neither early nor late stages, which confirmed the previous research results obtained by our group [ 57 , 58 ].…”
Section: Discussionsupporting
confidence: 92%